Influence of respiratory instability during neurocardiogenic presyncope on cerebrovascular and cardiovascular dynamics. Issue 11 (18th October 2007) - Porta, C; Casucci, G; Castoldi, S; Rinaldi, A; Bernardi, L
Abstract : Objective: To analyse the influence of breathing activity on cerebrovascular dynamics during presyncope. Design: Retrospective study. Setting: University hospital. Patients: 38 subjects developing neurocardiogenic syncope (syncope group), and 61 age-matched control subjects with negative tilt. Interventions: Middle cerebral artery mean blood flow velocity (MCFV), continuous non-invasive blood pressure (BP), end-tidal CO2 (CO2 -et) and minute ventilation were measured before and during 45′ 60° tilting. Main outcome measures: Respiratory and cerebrovascular variability, cerebrovascular resistance (CVR)—absolute and corrected for CO2 -et at 40 mm Hg (CVR-40)—and dynamic cerebrovascular regulation (CVR-dyn: transfer function phase analysis between MCFV and BP), obtained during supine rest (baseline), first 5 minutes of tilt (early tilt), early- and late presyncope (first and second half, respectively, of 4 minutes preceding syncope in syncope group, and equivalent time in controls). Results: Tilting induced a mean (SE) CVR decrease in controls (baseline 1.20 (0.04); late presyncope 1.12 (0.06) mm Hg × s/cm, p<0.05) but not in the syncope group (baseline 1.09 (0.04); late presyncope 1.09 (0.06) mm Hg × s/cm, p = NS). However, CVR-40 showed similar reduction in both groups (controls: from 1.15 (0.04) to 0.96 (0.04) mm Hg × s/cm; syncope group: from 1.01 (0.04) to 0.83 (0.04) mm Hg × s/cm, p = NS). CVR-dyn of the two groups was also similar (p = NS). Respiratory variability increased in the syncope group, from early tilt to late presyncope (p<0.05 or better), preceding hyperventilation and being significantly correlated with an increase in MCFV and BP variability (p<0.01). Conclusions: During presyncope, the development of respiratory instability and hypocapnia impairs MCFV, thus facilitating the onset of syncope despite preserved cerebrovascular regulation.